Rebel Buddha : a guide to a revolution of mind - Dzogchen Ponlop, Rinpoche, 1965- (Shambhala, 2011)
There's a rebel within you. It's the part of you that already knows how to break free of fear and unhappiness. This rebel is the voice of your own awakened mind. It's your rebel buddha--the sharp, clear intelligence that resists the status quo. It wakes you up from the sleepy acceptance of your day-to-day reality and shows you the power of your enlightened nature. It's the vibrant, insightful energy that compels you to seek the truth.